Mucinous Borderline Tumor with Carcinosarcoma Mural Nodule: A Case Report - Bhatta, Uma; Sharma, Nisha; Mahat, Smritee (Journal of Karnali Academy of Health Sciences, 2022)
Mucinous borderline tumor with carcinosarcoma mural nodule is a very rare neoplasm with only a few cases reported in the literature so far. Diagnosis is based on clinical evaluation, radiological findings, and histopathological features in conjunction with immunostaining with specific markers. A 71-year-old woman was presented with a history of gradual onset of abdominal distension, nausea, and vomiting. A physical examination revealed a hard, palpable mass with mild tenderness in her right lower abdomen. USG and CT demonstrated a large complex mass in the ovary. The patient underwent left salpingo-oophorectomy. A case of mucinous borderline tumor with carcinosarcoma mural nodule was reported and staged as pT1c2Nx/FIGO Ic according to 8th edition AJCC (American Joint Committee on Cancer).